Laboratory Performance Evaluation of Co-Polymer Based Dust Suppressant Mixed with Poorly Sand. Issue 5 (September 2019) - Wu, Ziyan; Ho, Chun-Hsing; Huang, Junxin
Abstract: Fugitive dust, generated along unpaved roads or uncovered construction sites, defined as a type of atmospheric matter (PM), is considered as a major source of air pollution in metropolitan areas. Fugitive dust can potentially cause respiratory illness and lung damage for humans, and even lead to premature death in sensitive individuals. Aiming to reduce the fugitive dust emission on unpaved roads, scientists did various lab experiences to analyse the performance of different types of dust suppressants mixed with different soils. In our previous papers, we evaluated the co-polymer-based dust suppressant (CPS) mixed with loamy sand (soils are from Sedona, Arizona) and silty clay (SP-SC) (soils are from Flagstaff, Arizona). The objective of this paper is to analyse the efficiency of fugitive dust reduction and present the quantitative laboratory evaluation of CPS mixed with poorly sand (SP). The soils were sampled from Page, Arizona. Soil classification is based on United Soil Classification System (USCS). Four concentrations of CPS (0%, 1%, 3%, and 5% by weight) were diluted and mixed with soil samples to prepared soil specimens. A series of laboratory experiences were performed on the soil specimens including moisture retention test, surface strength test, dynamic rolling test, and scanning electron microscopy (SEM) imaging. The laboratory results show that the higher the concentration of CPS is, the better CPS performs, and CPS with 5% concentration by weight controls the dust emissions better as compared with the other three concentrations, provided the results from the moisture retention rate, surface strength, dynamic rolling resistance, and interlock/cohesion effect in SEM images are promising.